Studium tvorby a kinetiky hydratace belitického slínku - Halešová, Adéla (Vysoké učení technické v Brně. Fakulta stavební, 2017)
DIPLOMOVÁ PRÁCE SE ZABÝVÁ STUDIEM PŘÍPRAVY ČISTĚ BELITICKÉHO SLÍNKU ZA ÚČELEM POTENCIONÁLNÍHO ZVÝŠENÍ KINETIKY HYDRATAČNÍCH PROCESŮ FORMOU CHEMICKÉ AKTIVACE. PRÁCE JE VYPRACOVANÁ FORMOU REŠERŠÍ O ZJIŠTĚNÝCH DOSAVADNÍCH POZNATCÍCH NA ZÁKLADĚ DOSTUPNÉ LITERATURY A VÝSLEDKŮ VÝZKUMU NA ÚSTAVU THD. CÍLEM DIPLOMOVÉ PRÁCE JE NÁVRH SLOŽENÍ SUROVINOVÉ MOUČKY PRO VÝPAL BELITU, NÁSLEDNÁ MODIFIKACE MOUČKY SÍRANEM A UHLIČITANEM DRASELNÝM ZA ÚČELEM POTENCIONÁLNÍHO ZVÝŠENÍ REAKTIVITY VYPÁLENÉHO BELITICKÉHO SLÍNKU A LABORATORNÍ VÝPAL PŘIPRAVENÝCH SUROVINOVÝCH MOUČEK. POSLEDNÍM KROKEM BYLO VYHODNOCENÍ MINERALOGICKÉHO SLOŽENÍ VYPÁLENÝCH VZORKŮ XRD ANALÝZOU A NÁSLEDNÉ SROVNÁNÍ PARAMETRŮ ZÁKLADNÍ BUŇKY U BELITU S A BEZ PŘÍDAVKU MODIFIKUJÍCÍCH PŘÍSAD.

DIPLOMA THESIS IS DEVOTED TO THE STUDY OF PREPARATION OF PURE BELITE CLINKER FOR THE POTENTIAL INCREASE OF KINETICS OF THE HYDRATION PROCESS BY CHEMICAL ACTIVATION. THE THESIS OF THIS WORK IS BASED ON RESEARCH FINDINGS CONCERNING BELITE CLINKER AND RESEARCH AT THE INSTITUTE OF THD. THE THESIS AIMS TO DESIGN COMPOSITION OF THE RAW MEAL BURNING BELITE, FOLLOWING MODIFICATION BY SULPHATE AND POTASSIUM CARBONATE IN ORDER TO POTENTIALLY INCREASE THE REACTIVITY OF THE BURNT BELITE CLINKER AND THE LABORATORY FIRING OF PREPARED SAMPLES. THE LAST STEP WAS TO ASSESS THE MINERALOGICAL COMPOSITION OF BURNED SAMPLES XRD ANALYSIS AND FOLLOWING COMPARISON CELL PARAMETER OF BELITE WITH AND WITHOUT ADDED MODIFYING ADDITIVES.
Studying Formation and Kinetics of Belite Clinker Hydration
Keywords: BELITICKÝ CEMENT; SLÍNEK; HYDRATACE SLÍNKOVÝCH MINERÁLŮ; DIKALCIUM SILIKÁT; FÁZOVÉ SLOŽENÍ; BELITE CEMENT; CLINKER; HYDRATION OF CLINKER MINERALS; DICALCIUM SILICATE; PHASE COMPOSITION